Standar Operasional Prosedur Pelayanan Wisatawan di Pandan View Mandeh, Sumatera Barat - Fauziah, Qori; Putra, Trisna (Lembaga Yasin AlSys, 2023)
Standard Operational Procedure (SOP) is a work structure for professional work. The goal of this final project is to design an SOP that is applied when handling guests at Pandan View Mandeh. The design of the work is carried out with the stages of the process and the application of the implementation methodology with the stages of 1) Time and place of implementation of the work, 2) Design of the work design, 3) Validation, 4) Materials and Tools, 5) Work steps, 6) Budget Plan, 7) Implementation of Works. The work that has been carried out by observing, interviewing, and documenting the implementation of guest services at Pandan View Mandeh is the Standard Operating Procedure (SOP) that is applied at Pandan View Mandeh.